Specialty of Concept "Creativity " in Architecture - Maysoon Safi yaser (Iraqi Journal of Architecture and Planning, 2009)
Architecture is one of the most effective changing methods in society. It's a culturalphenomena that reveal thoughts and believes of its society through its production. Thatproduction must have the power to introduce the unique, and which never been known. Toachieve that is what could be named "Creativity".The object of this research is concemed with clarif,ing the concept ,,Creativity,, ingeneral, and its specialty in Architecture.The method which have been followed was by: l. Clarifying the concept in philosophy and linguistics theories because of itsinfluence on Architecture.2. Clarifuing the concept in different theoretical attitudes and strategies that havebeen used in Architecture.The research concluded that Creativity could be meaning both Revealing andcreation. The Revealing would be reached by passed over what have been kaown, and theCreation would be by displacement what has been known.